Well test model of vertical double-hole channeling considering gravity - XU Yandong, TAO Shan, HE Hui, WAN Xiaoyong, ZOU Ning, YUAN Hongfei (Youqicang pingjia yu kaifa)
The fault-affected karst system in the north of Shuntuoguole low uplift, Tarim basin, Shunbei oilfield has obvious vertical development and heterogeneity. Due to the large vertical depth of the reservoir, the influence of gravity can not be ignored in the process of fluid flow. Considering that the reservoir is composed of small-scale fracture, large-scale cavity and large-scale channeling path, and the initial pressure at different depths varies with the depth, a large-scale fracture-vuggy well test model considering gravity is established combined with the principle of seepage mechanics and the equipotential body theory. The Laplace transform method was used to address this issue and the typical model plate and parameter sensitivity analysis plate were drawn. The results show that the fluid flow needs to overcome more resistance when gravity is taken into account, and the positions of dimensionless pressure and its derivative curves are higher in the middle and later stages. When accounting for the seepage effect in small-scale fractured reservoirs, distinct flow characteristics emerge: Linear flow in channeling paths, Transitional flow in large cavities, Quasi-steady flow in large cavities, and Radial flow in fractured reservoirs. The slope of the dimensionless pressure and its derivative curve of the former is between 0 and 0.5. The dimensionless pressure derivative curves of the latter two decrease slowly and then rise slowly. The applicability and validity of the model are further corroborated through case studies. This research not only enriches the fracture-vuggy well test model literature but also provides a solid theoretical foundation for interpreting well test data in vertical fracture-vuggy reservoirs with significant depth.